2014
DOI: 10.1123/jpah.2014-0184
|View full text |Cite
|
Sign up to set email alerts
|

Results from the United States’ 2014 Report Card on Physical Activity for Children and Youth

Abstract: Background:The National Physical Activity Plan Alliance partnered with physical activity experts to develop a report card that provides a comprehensive assessment of physical activity among United States children and youth.Methods:The 2014 U.S. Report Card on Physical Activity for Children and Youth includes 10 indicators: overall physical activity levels, sedentary behaviors, active transportation, organized sport participation, active play, health-related fitness, family and peers, school, community and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 43 publications
3
43
0
1
Order By: Relevance
“…However, with the Chinese economy booming and the automotive industry developing, more and more people own their own car, especially in big cities like Shanghai. The current study revealed that 37.7% of students travel to school in the family car, which is lower than in US, 16 but higher than in Finland. 17 Sedentary Behavior: F For Sedentary Behavior, students were asked to report how many hours they spent watching TV/film, playing computer/video games, surfing the internet, and doing homework per day, both on weekdays and weekend days.…”
Section: Active Transportation: C-mentioning
confidence: 88%
“…However, with the Chinese economy booming and the automotive industry developing, more and more people own their own car, especially in big cities like Shanghai. The current study revealed that 37.7% of students travel to school in the family car, which is lower than in US, 16 but higher than in Finland. 17 Sedentary Behavior: F For Sedentary Behavior, students were asked to report how many hours they spent watching TV/film, playing computer/video games, surfing the internet, and doing homework per day, both on weekdays and weekend days.…”
Section: Active Transportation: C-mentioning
confidence: 88%
“…The individual country report cards discussed a variety of policies, strategies, and investments related to different indicators and collectively represent a catalog of ideas for governments to consider. 1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Many countries had relatively high grades for the policy environment both in schools and in governments, but relatively low grades for the indicators of health behaviors that the policies were targeting. Whether this reflects ineffective policies, lack of implementation or the reactive nature of policy development is unclear.…”
Section: Who Is Leading and Lagging?mentioning
confidence: 99%
“…54 In contrast, in the United States < 15% of children and youth used active transportation to get to and from school. 22 The most robust data available in most countries related specifically to active school transportation. 55,56 The percentage of children and youth in Canada, the United States, the United Kingdom, Australia, and New Zealand who cycled to/from school was generally low, whereas the prevalence of cycling or walking to/from school in countries from continental Europe and in China was relatively high compared with what is seen in North America, the United Kingdom, and Australasia.…”
Section: Who Is Leading and Lagging?mentioning
confidence: 99%
See 1 more Smart Citation
“…Current worldwide data suggest that only 5% to 50% of children and adolescents are meeting physical activity guidelines (60 minutes each day), implying that permanent adoption of daily physical activity and exercise in these populations may be difficult. [51][52][53][54][55][56] Supervision and enjoyment are components positively related to adherence, and consideration must be made when designing a training program. Watts et al 11 designed a game-based exercise program involving activities such as dodge-and-tag, jogging, and soccer, which resulted in a high attendance rate.…”
Section: Feasibilitymentioning
confidence: 99%